Dampak Produk Impor Terhadap UMKM Lokal di Indonesia - Septiannisa Paramita; Hikmayani Subur (Indo Publishing, 2026)
This study aims to analyze the impact of imported products on local MSMEs in Indonesia through a qualitative literature review approach. Globalization and trade liberalization have increased the inflow of imported products that are more competitive in terms of price, quality, and variety, thereby creating pressure on the competitiveness of MSMEs.The findings show that the increasing presence of imported products has an impact on the declining demand for local products, which in turn leads to decreased sales, income, and business sustainability among MSMEs. In addition, changes in consumer preferences, along with the limited capacity of MSMEs in innovation, technology, and management, further weaken their position in global competition. Nevertheless, MSMEs still have opportunities to survive through improving product quality, innovation, and the use of digital technology. Government policy support is also needed to strengthen the competitiveness of MSMEs amid the flow of global trade.